2008
DOI: 10.1051/0004-6361:20079249
|View full text |Cite
|
Sign up to set email alerts
|

A long-term photometric study of V 1184 Tauri

Abstract: Aims. The main purpose of our investigation is to construct the long-time light curve of the PMS star V 1184 Tau. We consider the study of the photometrical variability of PMS stars as very important for understanding stellar evolution. The unusual photometric variability of V 1184 Tau was reported in previous studies as well, but the nature of the observed deep minima is still under discussion. Methods. We present recent data from CCD photometry and from archival photographic plates. The photometric BVRI data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…Due to the complex circumstellar environment around PMS stars, such a mixture of different types of photometric variability can be expected. A similar superposition of two types of variability is seen on the long-term light curve of another PMS star V1184 Tau (Semkov 2006, Semkov et al 2008. But in this case the observed light curve is due to the phenomena of both: the typical for WTT stars periodic variability (Tackett et al 2003) and variable obscuration from UXor type (Barsunova et al 2006).…”
Section: Resultssupporting
confidence: 61%
“…Due to the complex circumstellar environment around PMS stars, such a mixture of different types of photometric variability can be expected. A similar superposition of two types of variability is seen on the long-term light curve of another PMS star V1184 Tau (Semkov 2006, Semkov et al 2008. But in this case the observed light curve is due to the phenomena of both: the typical for WTT stars periodic variability (Tackett et al 2003) and variable obscuration from UXor type (Barsunova et al 2006).…”
Section: Resultssupporting
confidence: 61%
“…In some cases, stars originally classified as FUors in the detailed spectral and photometric study were identified as variables of other types. Such an example is the case with V 1184 Tau, initially considered as a FUor, but according to the recent published results it is more likely a star of UX Ori type (Barsunova et al 2006;Semkov et al 2008). The photometric data for V 1735 Cyg collected up to the present have confirmed its FUor classi- fication.…”
Section: Resultssupporting
confidence: 53%
“…This should be an international cooperation study, because the archival photographic plates of this region have been stored in different countries. We are convinced that such a study would be very interesting and fruitful, as was the investigation of the suspected FUor star V 1184 Tau (Semkov et al 2008).…”
Section: Resultsmentioning
confidence: 92%
“…of observation, IRV B magnitudes of V1184 Tau, the telescope and CCD camera used. The mean values of instrumental errors of our photometric study are listed in Semkov et al (2008). In very deep minimums the star can be observed only in V, R, and I bands with the middle size telescopes (2-m RCC and 1.3-m RC) and only in R and I bands with the small telescopes (50/70-cm Schmidt and 60-cm Cassegrain).…”
Section: Resultsmentioning
confidence: 91%
“…In the third paper from our study (Semkov 2006), new data from optical photometry and spectroscopy of V1184 Tau in the period during the deep minimum are reported. In Semkov et al (2008), data from archival photographic plates are presented, which proves that an unknown minimum of brightness exists during the approximate period 1980-1985. Optical photometric data obtained at the time of our photometric monitoring have been published in Tackett et al (2003), Barsunova et al (2006), and Grinin et al (2009).…”
Section: Introductionmentioning
confidence: 89%